Struktura społeczna ludności tartezyjskiej na przykładzie cmentarzyska w Setefilla (prowincja Sewilla) - Krueger, Michał (Folia Praehistorica Posnaniensia, 2018)
The aim of this work is to present a general overview of social structure of the Tartessian community in Setefilla at the beginning of the Iron Age. The methodology is based on inductive approach, particularly on statistical and spatial analysis. Substantial research has been carried out on archaeological and anthropological data in order to determine indicators of sex and age. By using the achievements of postprocessual archaeology, I demonstrate the role of rituals and human body in creating social relations. It is argued that the traditional ties of consanguinity have been distorted by new social values built on individualism.